A critical comparison of the tribocorrosive performance in highly-alkaline wet medium of ultrafine-grained WC cemented carbides with Co, Co+Ni, or Co+Ni+Cr binders. (February 2021) - Boukantar, Aniss-Rabah; Djerdjare, Boubekeur; Guiberteau, Fernando; Ortiz, Angel L.
Abstract: The tribocorrosion (resistance, mode, and mechanism) of ultrafine-grained cemented carbides of WC-Co, WC-(Co+Ni), and WC-(Co+Ni+Cr) was evaluated and compared critically under the typical conditions of use in highly-alkaline wet medium by means of detailed studies of wet-sliding wear at pH ~ 13.65, complemented by separate detailed studies of both corrosion at pH ~ 13.65 and dry-sliding wear. It is shown that: ( i ) WC-Co undergoes the most severe tribocorrosion, and separately the most intense corrosion and little mechanical wear; ( ii ) WC-(Co+Ni) undergoes moderate tribocorrosion, and separately modest corrosion and little mechanical wear; and ( iii ) WC-(Co+Ni+Cr) undergoes only slight tribocorrosion, and separately almost negligible corrosion and very little mechanical wear. These observations were explicable in the framework of a conceptual model based on the different severities of the leaching of the binder pools and weakening of the WC/binder interfaces induced by corrosion, followed by material pullout (of both individual WC grains and/or large chunks of WC grains and binder) caused by frictional mechanical contact. It was also demonstrated that any of these three cemented carbides would be very useful for tribological applications because, despite their differences in performance, they all undergo just mild tribocorrosion and very mild dry-sliding wear. Nonetheless, WC-(Co+Ni+Cr) is to be recommended over both WC-Co and WC-(Co+Ni) for tribological applications in dry conditions, and is doubtless the cemented carbide of choice for tribological applications in alkaline corrosive media. Highlights: Alkaline tribocorrosion of WC-Co, WC-(Co+Ni), and WC-(Co+Ni+Cr) is evaluated and compared critically. WC-(Co+Ni+Cr) is the material of choice for tribological applications in alkaline media. WC-(Co+Ni) is preferable over WC-Co. WC-(Co+Ni+Cr) has greater resistance to both alkaline corrosion and dry wear than WC-(Co+Ni) and WC-Co. In terms of corrosion WC-(Co+Ni) is preferable over WC-Co, but in terms of dry wear both are equally recommendable. Tribocorrosion, corrosion, and dry wear of these cemented carbides occur similarly, but with varying severity depending on the binder. Alkaline tribocorrosion of these materials is mild, attesting as to why they are in such wide demand in industry. Dry-sliding wear is very mild.